2017
DOI: 10.1039/c7tb00700k
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of magnetic covalent organic frameworks for the hydrophilic enrichment of N-glycopeptides

Abstract: Magnetic covalent organic frameworks were synthesized as novel hydrophilic materials for specific enrichment of glycopeptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 39 publications
0
57
1
Order By: Relevance
“…Even when the total amount of human IgG decreased to 5 fmol, two glycopeptides could still be identified with S/N > 3 after enrichment by poly(GMA‐PETA‐CuMPc‐IDA) monolith. Compared with previously reported materials about the enrichment of glycopeptides from IgG digests, such as magnetic covalent organic frameworks Fe 3 O 4 @TpPa‐1 (28 fmol) , Au nanowires assisted magnetic graphene‐silica ZIC‐HILIC composites (10 fmol) , and MoS 2 /Au‐NP (gold nanoparticle)‐L‐cysteine nanocomposite (10 fmol) , this method had lower detection limits. The above results showed that the prepared poly(GMA‐PETA‐CuMPc‐IDA) monolith had higher detection sensitivity in enrichment of glycopeptides, demonstrating the application prospect in trace samples analysis.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Even when the total amount of human IgG decreased to 5 fmol, two glycopeptides could still be identified with S/N > 3 after enrichment by poly(GMA‐PETA‐CuMPc‐IDA) monolith. Compared with previously reported materials about the enrichment of glycopeptides from IgG digests, such as magnetic covalent organic frameworks Fe 3 O 4 @TpPa‐1 (28 fmol) , Au nanowires assisted magnetic graphene‐silica ZIC‐HILIC composites (10 fmol) , and MoS 2 /Au‐NP (gold nanoparticle)‐L‐cysteine nanocomposite (10 fmol) , this method had lower detection limits. The above results showed that the prepared poly(GMA‐PETA‐CuMPc‐IDA) monolith had higher detection sensitivity in enrichment of glycopeptides, demonstrating the application prospect in trace samples analysis.…”
Section: Resultsmentioning
confidence: 85%
“…The remarkable improvement of the enrichment performance could be attributed to the planar polar nitrogen groups and carboxy substituent of CuMPc which could form hydrogen bonds with hydroxyl groups of the saccharides . The outstanding hydrophilicity of the introduced IDA also contributed much to the enrichment capacity . Such results implied that poly(GMA‐PETA‐CuMPc‐IDA) monolith could be regarded as a promising material for glycopeptide enrichment.…”
Section: Resultsmentioning
confidence: 98%
“…The active sites in MPRs' structures are more accessible to substrates and hence provide superior catalytic activity. MPRs can be directly carbonized to ordered mesoporous carbons in a cost-effective manner [1][2][3]11,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, these processes may partially destroy the mesoporous structure in the MPRs. This results in ill-dispersed active catalyst sites [22][23][24][25][26]. The primary reason is attributed to the lack of appropriate sol-gel methods for precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Protein glycosylation, as one of the most important posttranslational modications (PTMs) of proteins, 1,2 is essential in various biological processes, such as molecular recognition, inner/intra-cellular signaling, immune response, and so on. 3,4 Sialylation of glycoproteins/glycopeptides typically occurs at the terminal of glycans, and the abnormal sialylated glycoproteins/ glycopeptides (SGPs) were related to a series of cancers and neurodegenerative diseases. 5 To better understand their biological activity, it is important to characterize the structure of SGPs.…”
Section: Introductionmentioning
confidence: 99%